MENEGUHKAN KEMBALI TRADISI PESANTREN DI NUSANTARA - Hasani Ahmad Said (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto Purwokerto, 2011)
This article shows the unique tradition at Islamic boarding schoolwhich is always interesting to dicuss. Many prominent people were bornand come from boarding schools. Meanwhile, nowadays there are somecritiques toward this institution related to its polarization. It could beunderstood as a way to face the social changes and modernisation. Thiscondition, influence its existence, dynamics, and institution’s role. Bydoing a library research about pesantren history, the writer beleives thatpesantren would be able to survive without losing its identity.